Peningkatan Keterampilan Berbicara Melalui Model Pembelajaran Student Facilitator And Explaining Siswa Kelas III SD Negeri 39 Pattongko Kecamatan Tellulimpoe Kabupaten Sinjai - Ismi Ismi; Nur Khadijah Razak; Desy Ayu Andhira (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to describe the improvement of speaking skills through the Student Facilitator And Explaining learning model for third grade students of SD Negeri 39 Pattongko Tellulimpoe District, Sinjai Regency. This type of research is classroom action research which consists of two cycles, each cycle is held three times a meeting. This research procedure includes planning, action implementation, observation, and reflection. The data sources of this research were 1 teacher and 21 students of class III of SD Negeri 39 Pattongko Tellulimpoe District, Sinjai Regency. The results showed that learning speaking skills through the Student Facilitator And Explaining learning model improved both in the planning, implementation, and evaluation stages. The assessment was carried out by paying attention to six aspects of assessment including speech accuracy, grammatical accuracy, speech fluency, word selection, mastery of topics, and voice volume also increased. The overall average student score in cycle I was 70.3 while the score in cycle II was 87.76 with a percentage increase of 17.46% which met the minimum completeness criteria (KKM) of 70. All aspects of the assessment were classified as moderate in cycle I and increased to a very high category in cycle II.